Using Public Key Algorithms in Cloud Computing Security - Masarath Begum; Komal; Shilpa Tarnalle (Current Approaches in Engineering Research and Technology Vol. 2, 2024)
Centered on its inherent data sharing and low latency features, cloud infrastructure is considered as an effective alternative to conventional information technology. Cloud service providers (CSPs) like Amazon, are capable of providing cloud users with various services by integrating powerful data centers. Users may utilize high-quality software to move their local data processing systems to cloud storage and save considerable investments in their local infrastructures. Annotation techniques by utilizing the pairs of meaning attributes are usually more descriptive, as they provide more details than the untyped methods. A new solution to use more concise queries with such annotations is the "pay-as-you-go" querying technique in data spaces.